Effects Of Starvation On Anammox Process And Bacteria - Shadan, Aidil Faizie (Universiti Sains Malaysia, 2018)
Anammox system contained ammonium and nitrite, as the only electron donor and electron acceptor, respectively, while carbonate was the only carbon source provided. The presence of nitrite and the absence of organic electron donors are essential for Anammox activity. Starvation studies have been carried out because bacterial starvation is a common phenomenon in nature and in wastewater treatment process, especially under conditions of varying influent and complicated environment in the biofilm. Three types of starvation were observed during this study, which is starvation of nitrite, starvation of ammonia and starvation of both nitrite and ammonia with addition of hydrazine. These types of starvation were investigated with same period of starvation time of 15 days at operating temperature of 35 ˚C. During the starvation period, the concentration of nitrogen component (ammonia and nitrite) in the wastewater were observed to study the effects of starvation to the Anammox process. While, Mixed Liquor Suspended Solid (MLSS), Mixed Liquor Volatile Suspended Solid (MLVSS) and extra polymeric substances (EPS) of the anammox bacteria was observed during the starvation period to study the effects of starvation to the bacteria. It have been found that, starvation of nitrite in the Anammox process gives small removal of ammonia concentration in the wastewater which is from 50 mg/L to 33.8 mg/L after the starvation period. While, starvation of ammonia and total starvation with addition of hydrazine result in total removal of nitrite and hydrazine respectively. Total starvation with addition of hydrazine give the highest concentration of MLSS and MLSS, which is 250 mg/L and 170 mg/L respectively.